Foxk1 and Foxk2 promote cardiomyocyte proliferation and heart regeneration - Dongcheng Cai; Chungeng Liu; Haotong Li; Chiyin Wang; Lina Bai; Jie Feng; Miaoqing Hu; Hao Wang; Shen Song; Yifan Xie; Ziwei Chen; Jiajun Zhong; et al. (Nature Communications)
Abstract Promoting endogenous cardiomyocyte proliferation is a promising strategy for cardiac repair. Identifying key factors that regulate cardiomyocyte proliferation can advance the development of novel therapies for heart regeneration. Here, we identify Foxk1 and Foxk2 as key regulators of cardiomyocyte proliferation, whose expression declines during postnatal heart development. Cardiomyocyte-specific knockout of Foxk1 or Foxk2 impairs neonatal heart regeneration after myocardial infarction (MI) injury. AAV9-mediated Foxk1 or Foxk2 overexpression extends the postnatal cardiomyocyte proliferative window and enhances cardiac repair in adult mice after MI. Mechanistically, Foxk1 and Foxk2 drive cardiomyocyte cell cycle progression by directly activating CCNB1 and CDK1 expression, forming the CCNB1/CDK1 complex that facilitates G2/M transition. Moreover, Foxk1 and Foxk2 promote cardiomyocyte proliferation by upregulating HIF1α expression, which enhances glycolysis and the pentose phosphate pathway (PPP), which further favors cardiomyocyte proliferation. These findings establish Foxk1 and Foxk2 as promising therapeutic targets for cardiac injury.